(untitled) (Journal of Advanced Veterinary and Animal Research, 2022)
Objective: The price of animal production will be affected by the significant increase in feed costs. The objective of this research was to investigate the impact of adding waste cassava pulp to fermented total mixed ration (FTMR) on nutrient utilization, rumen ecology, and microbial protein synthesis in tropical sheep. Materials and Methods: A 3 × 3 replicated Latin square design was used to randomly arrange nine crossbreed lambs (Santa Inês × Dorper) with an initial body weight (BW) of 18.7 ± 1.6 kg (mean ± SD). During a 21-day trial, the animal was offered a random selection of concentrate diets and rice straw (control), total mixed ration (TMR), or FTMR. During the investigation, data on nutrition utilization, rumen ecology, and microbial protein synthesis were analyzed using analysis of variance. Results: The finding shows that FTMR had significantly higher dry matter (DM) intake and DM intake per BW than either TMR or control (p < 0.05). Lamb fed on FTMR had significantly higher DM, organic matter protein, crude protein, and neutral detergent fiber digestion than those on control or TMR (p < 0.05). Rumen pH values for all treatments ranged from 6.68 to 6.73, with no significant differences. Growing lambs fed FTMR had greater rumen total volatile fatty acid and propionic acid concentrations than those given TMR and the control (p < 0.05). Protozoa were not different across the FTMR groups, although total bacterial and fungal zoospores were increased. In addition, when lambs were fed FTMR containing cassava pulp, ruminal microbial protein synthesis was significantly increased. Conclusion: It could indicate that feeding growing lambs with FTMR could improve nutrient utilization, ruminal fermentation, and microbial protein synthesis. However, studies on the effects of FTMR on sheep performance, meat quality, and milk quality are necessary. J. Adv. Vet. Anim. Res., 9(4): 754–760, December 2022 http://doi.org/10.5455/javar.2022.i645